Amazing grace adams eaudiobook A novel. - Littlewood, Fran (Macmillan Audio, 2023)
An Instant New York Times Bestseller A Today Read With Jenna Book Club Pick "I dare you not to fall wildly in love with Grace...It's a book about love, about grace, about even when we fall from those we love we can always find our way home...You will laugh on the first page and you will keep laughing until you're crying on the last page." ―Jenna Bush Hager, T he Today Show's #ReadwithJenna Bernadette , Eleanor Oliphant, Rosie, Ove . . . meet Amazing Grace Adams , t he funny, touching, unforgettable story of an invisible everywoman pushed to the brink—who finally pushes back. Grace Adams gave birth, blinked, and now suddenly she is forty-five, perimenopausal and stalled—the unhappiest age you can be, according to the Guardian . And today she's really losing it. Stuck in traffic, she finally has had enough. To the astonishment of everyone, Grace gets out of her car and simply walks away. Grace sets off across London, armed with a £200 cake, to win back her estranged teenage daughter on her sixteenth birthday. Because today is the day she'll remind her daughter that no matter how far we fall, we can always get back up again. Because Grace Adams used to be amazing. Her husband thought so. Her daughter thought so. Even Grace thought so. But everyone seems to have forgotten. Grace is about to remind them . . . and, most important, remind herself.